Mediation on the Matter of Parental Responsibility, the Concern of the European Judicial System of the New Millennium - Lenuța Giurgea; Carmen Ion (EIRP Proceedings, 2021)
In today's society, given the countless litigations involving minors and arduous litigation that is difficult to manage for the parties involved, all heavily burdening the work of the courts, at European level and not only specialists insist on alternative, non-contentious conflict resolution procedures. One of these effectively proven procedures is mediation. Given the very high mobility of citizens, both nationally and crossborder, the number of cases involving minors is steadily rising, thus cross-border mediation is giving proof of its increasingly effective role.